Influence of the last war in the study of tropical medicine and medical education generally - Arce, Julián (1920)
The stoppage of scientific progress, imposed by the terrible war which has now ended and directed all institutions and all energies toward the ultimate goal of complete destruction of implacable enemy, whatever the means by which it has come to an end, but in all the countries that took part in the conflagration, as many of them still suffer intense losses and the economic, industrial disturbances, political, etc., arising from such a great fight, some like the United States and England, whose powerful vitality, combined with practicality and resolved that characterizes them, allowed them to engage without delay to resume the work of its institutes and laboratories, for the cultivation of science, its applications and not the extermination of man, but the welfare and happiness of mankind.